Post-traumatic growth at the international level: The obstructive role played by translators and editors of Rwandan Genocide testimonies. Issue 1 (2nd January 2016) - Williamson, Caroline
Abstract : Between the months of April and July 1994, around 800, 000 people were murdered in what has become known as the Rwanda Genocide. In an attempt to record people's experiences and preserve the memory of this period of violence, the Genocide Archive of Rwanda, managed by the Aegis Trust, began collecting oral testimonies from those who survived. Many of these testimonies have subsequently been translated by the archive from Kinyarwanda into English and/or French and some have also been published in book format. This article analyzes processes of post-traumatic growth at an international level in the testimonies of female survivors. It reveals that although these women actively pursue agency (by holding the international community to account) and communion (by seeking to gain the international community's acknowledgement), their voices are being distorted by translators and editors who instead perpetuate the dominant Western understanding of survivors as passive, voiceless victims of an unavoidable period of violence.